2015
DOI: 10.4253/wjge.v7.i15.1191
|View full text |Cite
|
Sign up to set email alerts
|

Unsedation colonoscopy can be not that painful: Evaluation of the effect of “Lamaze method of colonoscopy”

Abstract: The performance of the "Lamaze method of colonoscopy" in the process of colonoscopy could relieve patients' pain, minimize the incidence of complications, and is worthy promotion in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The study results showed that there was no significant difference in age, gender, colonoscopy history, occurrence of complications, and time of the endoscope to reach the ileocecal junction between the two groups. Compared with routine nurse interventions for colonoscopy, Lamaze colonoscopy could significantly reduce the pain score of anal pain, descending sigmoid colon junction, splenic flexure, and hepatic flexure, which was consistent with findings of Yu et al and T. Voiosu et al [ 10 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The study results showed that there was no significant difference in age, gender, colonoscopy history, occurrence of complications, and time of the endoscope to reach the ileocecal junction between the two groups. Compared with routine nurse interventions for colonoscopy, Lamaze colonoscopy could significantly reduce the pain score of anal pain, descending sigmoid colon junction, splenic flexure, and hepatic flexure, which was consistent with findings of Yu et al and T. Voiosu et al [ 10 , 21 ].…”
Section: Discussionsupporting
confidence: 88%
“…Step D: halitus movement when feeling pain but unable to gather strength: to open the mouth and breathe rapidly like gasping with the body relaxed 2.3. Evaluation of Bowel Cleanliness [10]. All examined patients took the same laxative for bowel preparation, and the quality of preparation was graded as follows: grade I, excellent with no visible feces; grade II, satisfactory with a small amount of visible feces, but did not block the visual field; and grade III, unsatisfactory with feces blocking the visual field and/or colonoscopy passage.…”
Section: Modified Lamaze Breathing Methods Of Colonoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Amit Kumar, et al Unsedated Colonoscopy| Original Articlehad completion rate of 99% in their study 11,20. As per Yu et al the completion rate was 98% and there was high correlation between the Endoscopist and pain free examination of the colon till caecum 10. Completing the examination in single…”
mentioning
confidence: 86%